The association between the frequency of dental visits and independent factors among the adults aged 20 years and over in Serbia - Čanković, Dušan; Mastilović, Gorana; Čanković, Miloš; Radić, Ivana; Harhaji, Sanja; Čanković, Sonja (Vojnosanitetski pregled, 2021)
Background/Aim. Regular check-ups with a dentist are an important component of general oral hygiene habits. In addition to regular visits to a dentist, this includes the ongoing knowledge upgrade in the field of oral health as well as the application of preventive measures recommended by the selected dentist. The aim of this study was to determine the link between dental visits and independent sociodemographic factors and smoking in the adult population in Serbia. Methods. This cross-sectional study represents an analysis of 2013 National Health Survey for the population of Serbia (without the data on Kosovo and Metohija population). The study included 13,404 adults of 20 years of age and older. The mean age of participants was 51.7 years, including 7,221 (53.9%) females and 6,183 (46.1%) males. In order to determine possible predictors of a dental visit, a multivariate logistic regression model was implemented. A visit to a dentist was a dependent variable, while the independent variables were: sex, age, marital status, type of settlement, region, education, employment status, Wealth Index and smoking status. Results. Significant differences were observed between categories of dental visit and all independent variables except marital and smoking status. In the multivariate model, the odds of visiting a dentist in the period “12 months or longer” vs. “in the last 6 months” were the highest among older respondents [odds ratio (OR) = 1.03; 95% confidence interval (CI) = 1.02–1.04], from a rural area (OR = 1.17; 95% CI = 1.03–1.32), with a low (OR = 2.55; 95% CI = 2.12–3.07) and middle education level (OR = 1.76; 95% CI=1.54–2.00), the unemployed (OR=1.20; 95% CI = 1.06–1.37), those who belong to poorer (OR = 1.30; 95% CI = 1.08–1.54) or the poorest class (OR = 1.71; 95% CI = 1.38–2.12) and smokers (OR = 1.13; 95% CI = 1.01–1.26). Conclusion. The study demonstrated that sociodemographic factors and smoking are important factors related to a visit to a dentist. This study can help to advance regular visits to a dentist and programs of health education focusing on oral health and smoking cessation as well.
Keywords: adults; oral health; dentists; office visit; sociological factors; smoking; serbia